Upaya Peningkatan Kesehatan Ibu Dan Anak Yang Service Excellent Melalui Edukasi Pengetahuan Penyulit Kehamilan Dengan Sigap Resti Di PMB Marshinta Sirait Medan Polonia Tahun 2024 - Sonia Novita Sari; Ariska Fauzianty; Srilina Br Pinem; Nova Isabela Mariance Br Napitupulu; Diah Pitaloka Tarigan; Leni Oktafianti (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Parameters for measuring public health conditions can be studied through the maternal mortality rate (MMR) and infant mortality rate (IMR) that occur in each period. Education is one of the efforts to improve the level of health, increasing knowledge about health will change a person's attitudes and behavior regarding health. Health. Apart from using the lecture method, providing this education also provides leaflets to support the education. This community service activity is carried out by providing education through lectures assisted by modified media about risky pregnancies, complications of pregnancy, as well as about strengthening the detection of complications with alacrity and rest. Method: This activity begins with the preparation, implementation and evaluation stages. Results: 15 participants in this activity were pregnant women who visited the Marsinta Clinic in Polonia District, Medan City. In its implementation, risky pregnancies, complications in pregnancy are explained as well as strengthening understanding about fast rest as an empowerment for pregnant women in improving their health. Conclusion: The results obtained from this community service activity were an increase in knowledge about risky pregnancies before and after, namely an increase of 15% for the good level of knowledge, and 27% for the sufficient level, and at the level of poor knowledge there was a decrease of 40%. With this change in the level of knowledge and the strengthening of understanding, it is hoped that pregnant women will be more aware of the condition of their pregnancy and carry out pregnancy checks more regularly.